Development of a 2-D drawing bot - Karunarathne, Kumarapeli Arachchige Pavan Udana; Bohez, Erik L.J.; Manukid Parnichkun; Lin, Than (Pathum Thani, Thailand : Asian Institute of Technology, 2015)
The capstone project discusses the development of a 2D drawing robot using arms. It uses principles of Robotics engineering and principles of inverse kinematics to draw simples shapes such as straight lines, squares. The project describes the scope, objectives and limitations involved. Also the methodology.
A capstone project report submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering Mechatronics, School of Engineering and Technology
Capstone Project (B. Sc.) - Asian Institute of Technology, 2015
Keywords: Two-dimensional imaging; Robotics